1974
DOI: 10.1159/000459416
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal β-Galactosidases in Adult Low Lactase Activity1 and in Congenital Lactase Deficiency

Abstract: Three different β-galactosidases in the human small intestine have been partially purified and characterized. Quantitative methods, applicable on single jejunal biopsies, were then elaborated to study the enzymatic alteration in adult low lactase activity and in congenital lactase deficiency. The activity of brush-border lactase was 10-20 times reduced in adults with specific low lactase activity. The residual enzyme had the same properties as in adults with persistently high lactase activity. In three patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…As some minor bands were observed in the electrophoresis gel, a method developed by A. Dahlqvist [30, 311 was followed to prove that no other intestinal P-galactosidases were present in the preparation. Thus, o-nitrophenyl-fi-u-galactopyranoside and p-nitrophenyl-P-D-galactopyranoside were substrates for the enzymic activity, while 2-napthyl-P-~-galactopyranoside was not a substrate, as should be expected if only lactase activity is present [31]. Equally, p-chloromercuribcnzoate did not inhibit the P-galactosidase activity of this preparation, as has been described for lactase activity [30].…”
Section: Resultssupporting
confidence: 65%
“…As some minor bands were observed in the electrophoresis gel, a method developed by A. Dahlqvist [30, 311 was followed to prove that no other intestinal P-galactosidases were present in the preparation. Thus, o-nitrophenyl-fi-u-galactopyranoside and p-nitrophenyl-P-D-galactopyranoside were substrates for the enzymic activity, while 2-napthyl-P-~-galactopyranoside was not a substrate, as should be expected if only lactase activity is present [31]. Equally, p-chloromercuribcnzoate did not inhibit the P-galactosidase activity of this preparation, as has been described for lactase activity [30].…”
Section: Resultssupporting
confidence: 65%
“…It could be demonstrated that adults with low lactase activity had a variable residual activity of seemingly normal Scand J Nutr/N%ringsforskning 4/01 lactase, whereas no residual activity could be measured in cases of congenital lactose malabsorption (10). Immunoelectrophoretic studies by Skovbjerg, Sjostrom, Nor&, Gudmand-Hoyer and Fenger (1 l,l2) confirmed that low lactase activity in adults is due to a small amount of normal lactase and not to a modified inactive enzyme.…”
Section: Digestion and Absorption Of Lactosementioning
confidence: 94%
“…The lactase was characterized in more detai l and separated fro m other smal l intestinal !3-galactosidases (17) , and analyses of the thre e different small intestina l mucosa l !3-galactosidases in small intes tinal biopsies from patie nts with low lactase activit y showed that there was a decrease in the bru sh border lact ase but not in the other !3-galactosidas es (18). On the other hand , children with congenital lactase deficiency had practically no brus h-border lactase activit y left (19) .…”
Section: Dedication To Arne Dahlqvistmentioning
confidence: 98%